Evaluating The Quality of Blended Learning Strategy Based Module for Islamic Civilization and Asian Civilization Course: Mengevaluasi Kualitas Modul Berbasis Strategi Pembelajaran Campuran untuk Peradaban Islam dan Kursus Peradaban Asia - Mohd Burhan, Norhapizah; Zabidi Mahfuzah , Mohamed; Mohamed, Asjad; Mohd Kamal Azman Jusoh; Mohd Nasir Ayub (Halaqa: Islamic Education Journal, 2020)
This study aimed to evaluate the digital learning content for Islamic Civilization and Asian Civilization (TITAS) course based on Blended Learning strategy at one of the public univer- sities in Malaysia. This research adopted Type 1 developmental research design in which its formative evaluation phase involved an alpha and beta testing to elicit responses to the module. The instruments used were expert evaluation form, questionnaires, and the digital learning module prototype software. A total of nine (9) experts from public universi- ties in Malaysia and fourty (40) undergraduate university students from UniversitiTeknologi MARA took part as purposive sampling. The usability of the digital learning module was seen relative in terms of `flexibility' and `learning community' aspect which obtained the highest mean (mean = 5.00) among experts. Whereas students had different perception on factor contributed to the students' usage of the digital learning module, which they equally found that `flexibility' aspect obtained the highest mean (mean = 3.93), followed by the aspect on `personel learning' (mean = 3.90) and `complementary learning' (mean= 3.88). In addition, content experts recommended aspect of values need to exert in the digital learning module, while technological and blended learning experts stated that the design, interactivity, guidelines and links required some improvements to produce a better module for TITAS. Overall, this study contributes to the development of blended university compulsory course for TITAS based on users' need.